The taxation of equity, dividends, and stock prices - Richard W. Kopcke (Federal Reserve Bank of Boston, 2005)
The Jobs and Growth Tax Relief Reconciliation Act of 2003 (JGTRRA) essentially halved the tax rate on dividends and reduced the top tax rate on capital gains. This paper explores the likely effect of JGTRRA on the composition of returns on corporations' common stock. Both larger corporations' past behavior and theory suggest that the recent tax cuts are not likely to increase dividend payouts significantly. Instead, in the short run, dividends will continue to rise in the customary way in response to the recovery in earnings. In the longer run, the tax cuts will principally reduce companies' cost of capital, fostering capital deepening, when the economy is at full employment. With constant returns to scale prevailing at full employment, capital deepening reduces corporations' average gross return on assets and equity. Because the tax cuts increase the value of each dollar of earnings for shareholders, they could raise price-earnings ratios by more than 10 percent and stock prices by more than 6 percent. By fostering capital deepening, the tax cuts also tend to increase the real compensation of labor at full employment.
Keywords: H25; H71; O10; 330